Morphology profiles generated by temperature gradient in PMMA modified epoxy system - Stefani, Pablo Marcelo (2001)
A diglycidyl ether of bisphenol-A (DGEBA) epoxy resin was modified with 15 wt% of poly(methylmethacrylate) (PMMA) and cured with a stoichiometric amount of 4, 4′-diamino diphenyl methane (DDM). The reactive mixture was cured in a heated mold with different gradients of temperature. Temperature profiles in the mold were imposed by generation of a heat flux from the base, supported on a hot plate, and the top, cooled with water; they were measured along the mold. Depending on the thermal history in each position of the mold, the competition between the phase-separation process and reaction kinetics produces opaque or transparent zones. Phase separation can also occur in the postcure process while the gelation does not take place before. Therefore, a thermoset plate with gradient of morphology and properties was obtained. Mass fractions of PMMA dissolved in the matrix were calculated with the Fox equation from glass transition temperatures measured along the mold. They were related to morphologies developed during curing. The super-position of the phase diagrams with the conversion-temperature trajectories during cure permitted an explanation of the morphology gradients generated.